2011
DOI: 10.1002/macp.201100057
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Amine Methacrylate‐Based ABC Triblock Copolymers: Synthesis, Characterization, and Self‐Assembly in both Aqueous and Nonaqueous Media

Abstract: Water soluble poly[2‐(diisopropylamino)ethyl methacrylate]‐block‐poly[2‐(dimethylamino) ethyl methacrylate]‐block‐poly[2‐(N‐morpholino)ethyl methacrylate] triblock copolymers are synthesized via group transfer polymerization. They are molecularly soluble in acidic solution but give PDPA‐core three‐layer “onion‐like” micelles in alkaline solution. They also give two types of micelles in hexane depending on whether a cosolvent is used: i) PMEMA‐core “onion‐like” reverse micelles are formed with a cosolvent, or, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Even though, knowledge of polymer's salt‐responsivity is essential for in vivo applications, concerning the significant concentration of salts in blood plasma (mainly the concentration of NaCl is ≈ 0.1 m ). PMEMA's multiple stimuli‐responsivity was indeed highlighted in a series of publications about the schizophrenic micellization behavior of PMEMA‐containing block copolymers and triblock terpolymers …”
Section: Introductionmentioning
confidence: 87%
“…Even though, knowledge of polymer's salt‐responsivity is essential for in vivo applications, concerning the significant concentration of salts in blood plasma (mainly the concentration of NaCl is ≈ 0.1 m ). PMEMA's multiple stimuli‐responsivity was indeed highlighted in a series of publications about the schizophrenic micellization behavior of PMEMA‐containing block copolymers and triblock terpolymers …”
Section: Introductionmentioning
confidence: 87%
“…These authors found that both the N agg and R h of spherical core-shell micelles, having a P2VP-core and a corona of PS and PMMA, depend on the DP n of the insoluble P2VP sequence. Core-shell micelles, based on amino (meth)acrylates, were also obtained by Bütün et al [ 92 ] for poly[2-(diisopropylamino)ethyl methacrylate]-poly[2-(dimethylamino)ethyl methacrylate]-poly[2-( N -morpholino)ethyl methacrylate] (PDPA-PDMA-PMEMA) triblock terpolymers in hexane. In this case, the PDMA and PMEMA sequences are in the core of the micelles, which have a R h of 46 nm, whereas the PDPA block formed the solvated corona.…”
Section: Self-assembly Of Linear Abc Triblock Terpolymers In Organmentioning
confidence: 98%
“…The self-assembly of ABC terpolymers in organic solvent mixtures was performed essentially through the precipitation method starting from a homogeneous solution in a common solvent for all three blocks, followed by the addition of a non-solvent. As previously described, Bütün et al [ 92 ] studied the self-assembly of two PDPA-PDMA-PMEMA triblock terpolymers, not only in n -hexane, but also in a mixture of CHCl 3 / n -hexane, starting from a unimer’s solution in CHCl 3 . In this case, core-shell-corona micelles were obtained with a PMEMA core and a R h value of 15 nm.…”
Section: Self-assembly Of Linear Abc Triblock Terpolymers In Organmentioning
confidence: 99%
“…Especially o-nitrobenzyl chromophores are discussed as promising candidates for biological applications since even stimulation with NIR light is possible (see Section 3.3). Consequently, several block copolymers bearing o-nitrobenzyl ester groups in the side chain in combination with blocks of PEO/PEG or POEGMA [89][90][91][92][93][94][95][96][97], polystyrene [98][99][100], poly(methyl acrylate) [101], poly(2-ethyl-2-oxazoline) [102], or polydimethylacrylamide [103] have been synthesized and investigated towards their response upon irradiation with far UV light. Exemplarily, Liu and Dong showed the photo-controlled release of the anticancer drug doxorubicin from a biodegradable polypeptide-based poly(S-(o-nitrobenzyl)-L-cysteine)-block-poly(ethylene oxide) block copolymer.…”
Section: Irreversiblementioning
confidence: 99%